Abdominal multi-organ iron content and the risk of Parkinson’s disease: a Mendelian randomization study - Yang, Mingrui; Tang, Cheng; Peng, Fei; Luo, Chaotian; Chen, Guowei; Kong, Rong; Peng, Peng (Frontiers in Aging Neuroscience, 2024)
Background: To evaluate the causal relationship between abdominal multi-organ iron content and PD risk using publicly available genome-wide association study (GWAS) data.Methods:We conducted MR analysis to assess the effects of iron content in various abdominal organs on PD risk, followed by reverse analysis. Additionally, MVMR analysis evaluated the independent effects of organ-specific iron content on PD. We utilized genetic variation data from the UK Biobank, including liver iron content (n=32,858), spleen iron content (n=35,324), and pancreas iron content (n=25,617), as well as summary-level data for Parkinson's disease from the FinnGen (n=218,473) and two other large GWAS datasets of European populations (First dataset n=480,018; Second dataset n=2,829). The primary MR analysis used the inverse variance-weighted (IVW) method, confirmed by MR-Egger and weighted median methods. Sensitivity analysis was performed to address potential pleiotropy and heterogeneity. Observational cohort results were validated through replication cohort analysis, followed by meta-analysis.Results: IVW analysis revealed a causal relationship between increased liver iron content and elevated risk of PD (OR=1.27; 95% CI: 1.05-1.53; p =0.015). No significant causal relationship was observed between spleen (OR=1.00; 95% CI: 0.76-1.32; p =0.983) and pancreatic (OR=0.93; 95% CI: 0.72-1.20; p =0.573) iron content and increased risk of PD. Meta-analysis of GWAS data for PD from three different sources using the random-effects IVW method showed a statistically significant causal relationship between liver iron content and the occurrence of PD (OR=1.17, 95% CI: 1.01-1.35；p =0.012).Conclusion: This study presents evidence from Mendelian randomization (MR) analysis indicating a significant causal link between increased liver iron content and a higher risk of Parkinson's disease (PD). These findings suggest that interventions targeting body iron metabolism, particularly liver iron levels, may be effective in preventing PD.